The Role of the International Labour Organisation in Shaping Working Conditions in the Textile Industry - Miernicka, Irmina (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
Over the years, concerns about working conditions and labour rights within the textile industry have become increasingly prominent. Addressing these issues, the International Labour Organisation (ILO) has played a pivotal role in shaping and improving working conditions across the textile sector. This paper aims to explore the key legal regulations and non-legislative initiatives undertaken by the ILO. The author refers to the texts of the conventions, studies of the ILO and other organisations, as well as the literature on law. The research conducted indicates that the ILO’s actions positively impacted the textile industry’s labour practices globally. Nevertheless, the author argues that it is necessary to adopt a convention specifically dedicated to labour rights in the textile industry, thereby promoting fair and sustainable practices that benefit workers, businesses, and economies.